Case Report: Combination of Electrocautery and Echinacea Therapy in Condylomata Acuminata - Raras Pratita; Lita Setyowatie (Asian Journal of Health Research, 2022)
Introduction: Condylomata acuminata or genital warts are classified as sexually transmitted infections caused by the Human Papilloma Virus. The main purpose of Condylomata acuminata treatment is to remove warts and prevent recurrence. Monotherapy is often unsatisfactory. Combination therapy can be done for a better response and minimizing recurrences, one of which is by using an immunomodulator, namely Echinacea. Case Presentation: A 47-years-old woman, widowed, heterosexual, with complaints of genital warts since 2 months ago. Dermatovenerological examination on the major and minor labia showed papules with skin and mucosa color, verucose, multiple, no tenderness and no bleeding. Inspeculo examination found no lesions on the vaginal wall. The acetowhite test showed a positive white color. Patient was diagnosed with condylomata acuminata. The patient received electrocauter therapy once and Echinacea 500 mg for 3 months. Follow-up for 6 months did not reveal any new or recurrent lesions. Conclusion: Therapy for condylomata acuminata is still challenging. Monotherapy is often unsatisfactory due to high degree of recurrence. The use of combination therapy is aimed at minimizing recurrences, one of which is the use of imunomudulator. In this case report, there were no relapses in the 6th month of follow up with combination treatment. These case report can increase knowledge about therapeutic options for CA to avoid recurrences.